Acetic Acid Use in Chronic Wound Healing: A Multiple Case Series. Issue 3 (7th May 2022) - Chen, Qiuyun; Zhou, Kehua
Abstract : BACKGROUND: Acetic acid is bacteriostatic or bactericidal to many gram-negative and gram-positive microorganisms, especially Pseudomonas. Nevertheless, it has also been found to possess cytotoxic effects in concentrations as low as 0.25% inhibiting the epithelialization process during wound healing. CASES: In this multiple case series, we present 2 cases of chronic traumatic leg wounds treated with gauze moistened with acetic acid (0.25%), which were covered with a securing dressing and compression stockinet. Both patients were told to apply gauze moistened with acetic acid (0.25%) twice daily. In both cases, the wound progressed to blue-green drainage and wet yellow slough tissue to near-complete beefy granulation tissue. At this point, acetic acid was replaced with collagen or petrolatum dressing until complete wound closure was achieved. The treatment of these wounds illustrated successful use of acetic acid for chronic wound care. CONCLUSION: Our experience with these cases suggests that appearance of blue-green wound drainage and wet yellow slough tissue is a reasonable indication for the use of gauze moistened with acetic acid (0.25%). Further research is needed to test the efficacy of these principles in guiding acetic acid use in wound care.